Chapter Guidance Models and Practices Adopted Internationally to Promote the Exploration of Skills Relating to the Employability of Students with Disabilities. A First Meta-Analysis - Cesarano, Valentina Paola (Studies on Adult Learning and Education, 2018)
Employability is defined as an interweaving of a person's human, social and psychological capital, mediated by situational variables, which allows individuals to enter the job market with a professional personal project (Grimaldi, Porcelli, Rossi 2014). Nowadays, young people enter the job market through long, precarious, and poorly contextualized paths, while the socialization processes become recursive, discontinuous, and fragmented (Lodigiani 2010). A key role can be played by guidance services, which can start at university, to meet the demands of the (many) young people who are discouraged and disillusioned to the point where they cannot even imagine a job while still at university. In the employability stakes, what is even more complex is the encounter between young people with disabilities and the world of work, due to the persistence of stereotypes and stigmas. Research questions: What are the intervention models and guidance practices adopted by university guidance services internationally to promote the exploration of skills relating to the employability of students with disabilities? Objectives: To analyse the main intervention models and guidance practices adopted internationally to explore the skills associated with employability in students with disabilities. Methodology: It was decided to carry out a theoretical analysis of 20 scientific articles concerning the models and practices adopted to explore the competences relating to employability in certain university orientation services for students with disabilities in Italy, France, the UK, and the United States. NVivo software was used (Richards 1999) to systematically explore the scientific literature. Preliminary Findings: A first scientific paper showed that, like in Italy and France, the «Competence Balance Sheet» (Ardouin 2010) is the guiding practice in the USA, while in the UK, it is the Career Guidance Approach (Reid, Scott 2010). In the literature, orientation models and practices are also closely linked to the various patterns of employability. Final remarks: The implementation of guidance counseling paths aimed at exploring the skills associated with employability among all students and graduates is crucial to the completion of a viable strategic action in the University's social function, as a part of new organizational models that take the plurality of learning opportunities into account